STUDENTS’ AWARENESS AND PERCEPTION TOWARDS LEARNING STYLES - Safrul Muluk; Habiburrahim Habiburrahim; Siti Rechal Rechal (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2020)
Learning style is one of the significant elements in learning process that helps students achieve their learning goals. Nevertheless, students should be aware of their own style in learning which make them maximally enhance learning. Therefore, in study, the researcher examined students’ awareness of learning styles and their perception of their learning styles. A quantitative descriptive research was used in this study. Then, the data was collected through online questionnaire distributed for 100 students of fifth semester of English Language Education Department by using random sampling technique. VARK (Visual, Auditory, Reading, and Kinestetic) questionnaire created by Fleming and Likert scales were used to explore the issue under investigation. Findings of the research showed that students had moderate to high awareness of their learning styles. Within the context of this study, this findings were new in a way that it showed students’ perception on learning styles and how it affected their learning experiences. the Moreover, research findings also indicated that students believes that the learning styles they adopted helped them in achieving their learning goals supported by their learning environment. The result of the study indicated that students preferred visual learning styles.